Interlinked Marketing and Credit Arrangements: Some Recent Evidence from Rural Philippines - Robert Jr. Teh (Philippine Institute for Development Studies (PIDS), 1994)
The formal credit market has rationed out small-scale farmers due to asymmetry of information. Hence, interlinking of markets is observed. In this arrangement, traders become lenders to farmers due to informational advantages acquired through the years of transactions with each other. This research reports the two-phase survey results in the provinces of Bohol and Iloilo. In particular, this comprehensively describes the trader-farmer interlinked arrangements to determine the duration of the loans, the identity of the lenders, the form of payments, the methods of screening borrowers and the controls implemented to prevent moral hazard.
Keywords: 330; rural credit; interest rate; collateral; credit program; interlinked markets; rural sector; borrowing behavior; forward contracts